Role of Nd3+ concentration on the microstructure and scintillation behaviour of langbeinite sulphate (vol 284, 128997, 2021) - Poornima, Velswamy; Mohan, Subramaniam; Uma, Tiruchirappalli Sivagnanam (Materials Letters, 2021)

Role of Nd3+ concentration on the microstructure and scintillation behaviour of langbeinite sulphate - Poornima, Velswamy; Mohan, Subramaniam; Uma, Tiruchirappalli Sivagnanam (Materials Letters, 2021)
Langebeinite (K2Ca2(SO4)(3)) ceramics doped with increasing concentrations of Nd3+ ions (0.01-0.04 mol%) was prepared by wet chemical precipitation and calcination at 800 degrees C. Thermal studies revealed high temperature stability of the phosphors. UV-VIS-NIR spectroscopic analysis of phosphors reveal strong absorption peaks representing f -> f transitions. Direct bandgap derived from Kubelka-Munk plot was found to be similar to 5.66 eV. FTIR studies reveal tetrahedral symmetry of the SO42 ions. SEM micrographs reveal the formation of phosphors with wide particle size distribution and elemental composition was analysed using EDX studies. Scintillation studies representing a single high intensity peak around 784 nm is ascribed to I-4(9/2) -> F-4(5/2) + H-2(9/2) transition. Langbeinite phosphor with 0.02 mol% of Nd3+ exhibited maximum emission intensity indicating optimal concentration for scintillation studies favouring the development of NIR emitting phosphors. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Langebeinites; Luminescence; Microstructure; Neodymium; Scintillation

Exploring the structural and photophysical properties of tri-cation mixed halide double perovskites (Cs2AgIn0.85-XCeXBi0.15Cl6) for high-performance phosphor-based WLEDs - Ravi, Nalini; Kanapathi, Prakash; Mohan, Subramaniam; Appadurai, Tamilselvan (Dalton Transactions, 2025)
Owing to their superior optoelectronic properties, lead-free halide double perovskites (HDPs) have been extensively studied for a wide range of optoelectronic applications, especially for fabricating white light-emitting diodes (WLEDs). Considering white light emission, the HDP structure's dual octahedral configuration facilitates greater lattice distortion, thereby fostering strong electron-phonon coupling-derived self-trapped exciton (STE) emission upon photoexcitation. Herein, we propose facile fabrication of a highly feasible phosphor-converted white light LED and an intensive analysis of the structural, compositional and photophysical properties of a tri-cation mixed halide double perovskite. We chose Cs2AgIn0.85Bi0.15Cl6 as a potential candidate for electroluminescent-based white light LED devices as its composition exhibits high stability, direct-allowed transition, and a notable photoluminescence quantum yield. However, we incorporated a lanthanide ion (Ce3+) into this cubic HDP structure via tri-cation mixing at the B `' site (Cs2AgIn0.85-XCeXBi0.15Cl6) to internally disturb structural periodicity and further enhance STE emission. Initially, powder XRD revealed the lattice expansion induced by Ce3+ incorporation, while XPS and TEM verified the substitution of Ce3+ at the In3+ site. Meanwhile, compositional and optical studies established the role of Ce3+ in retaining the direct allowed transition by effectively replacing the In3+ site. Urbach energy (EU), a measure of energetic disorderness at band edges, was found to be significantly reduced, showing a value of 135 meV for the Ce-5% sample. Most significantly, PL emission studies revealed an appreciable enhancement in the PL intensity with a prolonged STE lifetime of 670 ns for Cs2AgIn0.80Ce0.05Bi0.15Cl6, indicating improved radiative recombination. Besides, excitation-dependent Pl and PLE studies revealed that the emission solely came from the STE states. Elaboratively, vibrational studies elucidated that the Ce-5% sample exhibited a restabilized elpasolite structure and enhanced lattice phonons, which ultimately helped in boosting STE emission, as proven by the Huang-Rhys factor (S = 13). Finally, an efficient and durable phosphor-converted WLED was fabricated, and its performance was assessed, revealing CIE coordinates of (0.35,0.32), a CCT of 4368 K, and an extremely high CRI (Ra) of 92. Thus, our work provides an exclusive strategy to enhance the STE emission for potential application in electroluminescent-based WLED devices.

Lattice dynamics and electron-phonon coupling in geometrically distorted halide double perovskites - Kanapathi, Prakash; Ravi, Nalini; Mohan, Subramaniam; Vijayan, Viswanathan; Appadurai, Tamilselvan (Journal of Physical Chemistry C, 2026)
Electron-phonon coupling is a critical factor in regulating the photophysical behavior of halide double perovskites (HDPs), influencing their emission broadening through lattice softness and exciton dynamics. In this work, we investigate four structurally distorted compounds, such as Cs2Ag0.4Na0.6InCl6, Cs2NaIn0.9Bi0.1Cl6, Cs2AgIn0.9Bi0.1Cl6, and Cs2Ag0.4Na0.6In0.9Bi0.1Cl6, prominent for their broad emission characteristics. Our combined experimental analysis and numerical models demonstrate that the electron-phonon coupling is dictated by the interplay between the sublattice distortion and the bonding nature between the metal and halide atoms, which vitally modulates the overall lattice softness and the resulting spectral broadening. The introduction of more ionic Na-Cl bonds in the HDP structure softens (weaker bonding) the lattice and enhances the phonon population, resulting in strong coupling between the electron and phonon, as quantified by the Huang-Rhys factor for Cs2NaIn0.9Bi0.1Cl6 (18.88), Cs2Ag0.4Na0.6InCl6 (17.64), and Cs2Ag0.4Na0.6In0.9Bi0.1Cl6 (14.46). Raman analysis further evidences Na-induced lattice softness with a 5 cm-1 red shift of the A1g mode in Cs2NaIn0.9Bi0.1Cl6, compared to Ag-containing HDPs. These findings highlight that Na-based compounds have stronger electron-phonon coupling than Cs2AgIn0.9Bi0.1Cl6. Furthermore, temperature-dependent phonon dynamics using the cubic anharmonic model and the three-phonon anharmonicity theory demonstrate that the distorted structures involve a phonon anharmonicity due to the thermal disorder. We show that strong coupling between the electron and the energetic phonon broadens the emission spectrum but suppresses the PL intensity. This quenching may arise from the excessive phonon-intervened nonradiative relaxations in the Na-rich compounds. By contrast, the temperature-dependent PL of Cs2Ag0.4Na0.6In0.9Bi0.1Cl6, a compound with maximum PL intensity, reveals the major contribution of optical phonon to electron-phonon coupling, which facilitated the efficient STE formation. This study highlights the significance of lattice softness to regulate the optoelectronic properties of the halide double perovskites, providing a design approach for compositional engineering towards high-performance optoelectronic devices.